Study of Dermatophytosis Prevalence in Patients Attendingy Dermatology Clinic at Tripoli Central Hospital - Abourghib, Taher Y.; Almskat, Mohamed T. (The Libyan Journal of Science, 2021)
The current study was performed to determine the prevalence of superficial fungal infections among patients attending Dermatology Clinic at the Tripoli Central hospital. A total of 122 cases were selected with an age range 7-75 years. They were tested for fungal skin infections using microscopic and laboratory methods. The Results demonstrated that all patients had dermatophytes infections. Tinea ungium was the most common type of clinical infections (39.34%), followed by Tinea capitis (31.14%), Tinea pedis (22.13 %) and Tinea faciei (7.37 %). The results indicate that Trichphyton violacenm was the most common etiological agent of dermatophyte infection (59.01%) followed by Microsprum canis (20.49%) Trichophyton rubrum (12.29%), Epidermophyton floccosum (4.09%) and Trichophyton menagrophtis (3.27 %). The findings of the current study showed that higher prevalence of dermatophytes was higher in rural areas than urban areas.